Enhancing clinical faculties’ knowledge, attitudes, and performance in clinical supervision: a workplace-based faculty development program using proctor’s model - Marzieh Sadat Minouei; Athar Omid; Nikoo Yamani; Peiman Nasri; Soleiman Ahmady (BMC Medical Education)
Abstract Background Clinical supervision is crucial for developing medical trainees’ independence. Faculty development programs can enhance faculty performance by changing their faculty attitudes and knowledge. This study examined the impact of such programs on pediatric faculty members’ supervisory knowledge, attitudes, and performance. Methods This was a quasi-experimental, pre-post, single-group study. The participants included 20 pediatric faculty members conveniently selected from the Isfahan University of Medical Sciences in Iran. The program’s design used the Proctor model and ASSURE instructional design model. The 34-day program was delivered in a blended format (online and workplace) and included feedback. An observational checklist was used to assess faculty performance, and a self-report questionnaire was used to measure faculty members’ knowledge and attitudes toward clinical supervision. Paired t-tests, independent t-tests, Spearman correlation coefficients, Cohen’s -d values, and descriptive statistics were used. Results The mean self-reported scores of knowledge (before: 5.55 ± 2.31, after: 8.25 ± 1.53) and attitudes (before: 4.07 ± 0.52, after: 4.28 ± 0.43) among faculty members increased significantly after the development program. Additionally, 90.63% of the faculty members applied the components of the Proctor model of clinical supervision. Conclusion These results suggest that structured faculty development programs can improve faculty knowledge, attitudes, and performance in clinical supervision.